When push comes to nudge: a Chinese digital civilisation in-the-making - Keane, Michael; Su, G. (SAGE PUBLICATIONS LTD, 2019)
© The Author(s) 2019. China’s emergence as a technological power is now unquestioned. Since the early 2000s, the Chinese government has invested heavily in information and communication technology. Rather than seeing the internet as a challenge to its hegemony, the government has allowed leading communications companies to offer new digital services, many of which enhance peoples’ lifestyles, while others allow people to express their loyalty to the nation. The Party-state has in the process found a new solution to asserting control. This article investigates the concept of a ‘digital civilisation’, in particular how civilisational discourses associated with the Party-state since the beginning of the economic reforms have found new applications in online technologies. It draws on the ancient metaphor of flood control to show how behaviour is redirected, or nudged, towards digital lifestyle choices. Examples discussed include the multiplicity of QR codes, mobile payments, the social credit system, the Strong Nation (xuexi qiangguo) app and the Huawei Harmony operating system (OS).